Quantitative radiomics analysis of imaging features in adults and children Mycoplasma pneumonia - Meng, Huan; Wang, Tian-Da; Zhuo, Li-Yong; Hao, Jia-Wei; Sui, Lian-yu; Yang, Wei; Zang, Li-Li; Cui, Jing-Jing; Wang, Jia-Ning; Yin, Xiao-Ping (Frontiers in Medicine, 2024)
Purpose:To explore the value of clinical features, CT imaging signs, and radiomics features in differentiating between adults and children Mycoplasma pneumonia,and seeking quantitative radiomic representations of CT imaging signs.: Retrospective analysis of 981 cases of mycoplasmal pneumonia patients from November 2021 to December 2023, including 590 internal data(adults:450,children: 140) randomly divided into a training set and a validation set with an 8:2 ratio, and 391 external test data(adults:121,children:270). Using univariate analysis, CT imaging signs and clinical features with significant differences (p<0.05) were selected. After segmenting the lesion area on the CT image as region of interest, 1,904 radiomic features were extracted. Then, Pearson correlation analysis (PCC)and THE least absolute shrinkage and selection operator (LASSO) were used to select the radiomic features. Based on the selected features, multivariable logistic regression analysis was used to establish clinical model, CT image model, radiomic model and the combined model. The predictive performance of each model was evaluated using ROC curves, and AUC, sensitivity, specificity, accuracy, and precision.The AUC between each model was compared using the Delong test.Importantly, the radiomics features and quantitative and qualitative CT image features were analyzed using Pearson correlation analysis and analysis of variance, respectively.Results: For the individual model, the radiomics model,which was built using 45 selected features,achieved the highest AUCs in the training set, validation set, and external test set, which were 0.995 (0.992, 0.998), 0.952 (0.921, 0.978), and 0.969 (0.953, 0.982), respectively. In all models,the combined model achieved the highest AUCs, which were 0.996 (0.993, 0.998), 0.972 (0.942, 0.995), and 0.986 (0.976, 0.993) in the training set, validation set, and test set, respectively. In addition, we selected 11 radiomics features and CT image features with a correlation coefficient r greater than 0.35.The combined model has good diagnostic performance for differentiating between adults and children mycoplasmal pneumonia, and different CT imaging signs are quantitatively represented by radiomics.